Cancer survivors' access to care and quality of life: Do sexual minorities fare worse than heterosexuals?. Issue 17 (20th May 2019) - Boehmer, Ulrike; Gereige, Jessica; Winter, Michael; Ozonoff, Al
Abstract : Background: Adults with poor access to care are known to have worse quality of life (QOL). The purpose of the current study was to determine differences in cancer survivors' access to care by sexual orientation and to examine the association between access to care and QOL. Methods: The current secondary data analysis used 4 years of Behavioral Risk Factor Surveillance System data regarding adult men and women who self‐reported a history of cancer. Among the 70, 524 cancer survivors, a total of 1931 self‐identified as sexual minorities, defined as lesbian, gay, bisexual, or other nonheterosexual orientation. Results: Sexual minority women had significantly more access deficits compared with heterosexual women (42.7% vs 28.0%; P  < .0001), whereas men of different sexual orientations had similar access to care. Among sexual minority women, those with access deficits had higher odds of poor physical QOL compared with heterosexual women (odds ratio [OR], 2.0 [95% CI, 1.2‐3.4] vs OR, 1.3 [95% CI, 1.2‐1.5]), poor mental QOL (OR, 1.8 [95% CI, 1.1‐3.1] vs OR, 1.5 [95% CI, 1.3‐1.7]), and difficulties concentrating (OR, 2.0 [95% CI, 1.2‐3.5] vs OR, 1.7 [95% CI, 1.4‐1.9]). Sexual minority men with access deficits had greater odds of difficulty concentrating compared with heterosexual men (OR, 4.3 [95% CI, 2.0‐9.3] vs OR, 1.5 [95% CI, 1.2‐1.9]). Among men, sexual minority status increased the odds of poor mental QOL (OR, 1.49 [95% CI, 1.11‐2.01]). Conclusions: Access to care among sexual minority cancer survivors needs improvement. Sexual minority women should be a focus of future research because their poor access to care more strongly relates to worse QOL. Abstract : Access to care is linked to cancer survivors' quality of life. This study identifies inequities in cancer survivors' access to care by sexual orientation and demonstrates that the association between access to care and quality of life is stronger for sexual minority cancer survivors compared with heterosexual cancer survivors.